2001
DOI: 10.1007/bf02235484
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation for fecal incontinence: Outcome in 16 patients with definitive implant

Abstract: Neuromodulation can be considered an option for fecal incontinence. However, an accurate clinical and instrumental evaluation and careful patient selection are required to optimize outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 16 publications
2
67
0
3
Order By: Relevance
“…The median follow-up period was 29.2 months (range 6.5-60.0) and the median period between the last AR and the PNE was 3 years (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. All had an intact anal sphincter determined by endo-anal ultrasound.…”
Section: Group Amentioning
confidence: 99%
See 1 more Smart Citation
“…The median follow-up period was 29.2 months (range 6.5-60.0) and the median period between the last AR and the PNE was 3 years (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. All had an intact anal sphincter determined by endo-anal ultrasound.…”
Section: Group Amentioning
confidence: 99%
“…In 1995, Matzel et al [12] published their results of SNM applied to faecal incontinence. Since then, many studies demonstrated the efficacy of SNM for the treatment of faecal incontinence [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…La NRS es una terapia de reciente desarrollo y la bibliografía acerca de esta no es extensa (9). Las series publicadas, todas ellas con escaso número de pacientes, muestran resultados similares en cuando a índices de eficacia en torno al 70% (13)(14)(15)(26)(27)(28). En nuestra serie, la NRS ha supuesto una reducción media del valor de continencia en la escala de continencia de Cleveland-Wexner del 67,53%, resultado equiparable a los objetivados por otros grupos.…”
Section: Discussionunclassified
“…Así, la neuromodulación de raíces sacras (NRS), con eficacia clínica demostrada ampliamente en la incontinencia urinaria (7,8), surge como una opción terapéutica reciente y en desarrollo para el tratamiento de la IF (9). A pesar de los escasos estudios publicados (no más de 300 casos en la bibliografía internacional), los resultados iniciales nos sugieren que nos encontramos ante una terapia eficaz con un prometedor futuro, y que las series extensas con seguimientos a largo plazo, acabarán por situarla en un lugar predominante dentro del arsenal terapéutico de la IF (9)(10)(11)(12)(13)(14)(15)(16). Presentamos nuestra experiencia inicial en el tratamiento de la IF mediante la NRS a través de los resultados de un estudio prospectivo realizado con 26 pacientes en cuanto a la variación en la escala de continencia de Wexner-Cleveland y a la capacidad para el retraso de la defecación tras un año de terapia con NRS, realizando además una revisión de las distintas opciones terapéuticas para la IF y mostrando nuestro algoritmo terapéutico para esta patología.…”
Section: Introductionunclassified
“…Sacral nerve stimulation (SNS) has been used since 1967 to activate bladder voiding (91,132,182,241), to treat bladder incontinence (20,34,44,59,78,108,119,120,122,221,229), to alleviate pelvic pain (1,38,190,279), to prevent fecal incontinence (50,(72)(73)(74)103,153), and to relieve constipation (56,128,133,134,161,166,167,186,189,248,252,272 (87,112,138,147,198,199,219) led to many devices (152,201) for improving walking (81,237), activating hand function (24) through voice commands (94), enhancing coughing (154), and even relieving seating pressures (65). Called neuroprostheses (25,193), these devices often are designed to correct specific deficits, such as foot drop (27,217,245) and hand grasp weakness (47,249,267).…”
Section: Peripheral Nerve Stimulationmentioning
confidence: 99%